HTC462: Basic Commercial Cookery / Faculty of Hotel & Tourism Management - UiTM, Faculty of Hotel and Tourism Management (2023)
This course is to give students the fundamental concept, skill and techniques of basic cooking and also expose students to basic kitchen management skill, to enable them to understand how professional’s kitchen functions and what are involved in running a professional kitchen.